Establishing the Basis for a Multi-Purpose Local Labor Market Information System Assessment of User Need and Data Availability. Final Report - Probst, George; Meredith, Dwight; North Carolina State Dept. of Administration, Raleigh ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
To develop a coordinated interagency effort to improve North Carolina citizen access to employment opportunities, a statewide assessment was conducted of the availability and need for local labor market information in 1977-1978. Need and availability was assessed across five state agencies--Vocational Education, Community Colleges, CETA (Comprehensive Employment and Training Act programs), Vocational Rehabilitation, and Employment Security at both state and local agency offices--by the new instrumentation created for this study. Results obtained made it possible to prioritize twenty-four data categories according to their relative importance to various agencies. These categories covered various demand and supply aspects of market information, such as employment patterns, turnover statistics, vacancies, characteristics of employed and unemployed or discouraged workers, education and training program characteristics, etc. A catalog of data holdings broken out by these categories and by specific data elements across agencies was then established, there being a match between available data documentation and informational needs identified. The study served as a catalyst to initiate a concerted approach to occupational information data needs and to implement the logical first step in developing a Multi-Purpose Occupational Information System capable of providing for the policy planning needs of public and private administrators and individual citizens' career decision needs. (The report includes a 32-page executive summary of data categories, 50-page needs assessment questionnaire, the catalog of data holdings, and 150 pages of tables analyzing agency information needs.) (CP)
Sponsoring Agency: Bureau of Occupational and Adult Education (DHEW/OE), Washington, DC.
Contract Number: G007702137.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Data Analysis; Data Collection; Employment Opportunities; Employment Patterns; Employment Statistics; Information Needs; Information Sources; Information Systems; Labor Market; Labor Needs; Labor Supply; Needs Assessment; Occupational Information; Occupational Surveys; Planning; Policy Formation; State Agencies; Statewide Planning; Systems Development; Tables (Data); Reports, Research; Numerical/Quantitative Data